Uncovering Anxiety in Science Education: Psychometric Validation of the Brief Science Learning Anxiety Scale (BSLAS) - Rizki Nor Amelia; Ani Rusilowati; Sri Rejeki Dwi Astuti; Ika Nur Fitriani; Arfatur Rohman; Mohammad Roy Thoriqul Haq (Jurnal Pendidikan IPA Indonesia, 2026)
Science learning anxiety can hinder pre-service teachers' engagement with scientific concepts and negatively affect their future teaching practices. However, instruments specifically designed to measure this construct in science education contexts remain limited. This study developed and validated the Brief Science Learning Anxiety Scale (BSLAS) to measure science learning anxiety among pre-service science teachers, based on Hooda and Saini's theory of academic anxiety. The development process involved five stages: scale design, item development, item selection, validation, and evaluation. Content validity was evaluated using Aiken's V, which indicated strong agreement among experts (V = .91). Exploratory factor analysis with 320 respondents identified five dimensions: worry, procrastination, study skills deficits, emotionality, and task-generated interference, explaining 49.04% of the variance. Confirmatory factor analysis on an independent sample of 324 respondents supported the factorial structure and demonstrated an acceptable model fit. The scale also demonstrated adequate convergent and discriminant validity and high internal reliability (ω = .847-.917). These findings indicate that the BSLAS has sound psychometric properties and can serve as a practical instrument for identifying science learning anxiety among pre-service teachers. The instrument may also support further research in science education and help inform teaching strategies that foster more adaptive science learning environments.